Predicting suicide attempts among teenagers in Bandar Abbas: The role of rumination and emotion regulation - Karami Beldaji, Roohollah; Ismaeili, Mahmoud; Beirami, Ashraf; Mirzadeh Baghdadi, Yasaman; Mazhari Azad, Fereshteh (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: Suicide attempts among teenagers are a significant public health concern, often linked to emotional and cognitive factors, such as rumination and emotion regulation. This study investigated the relationship between rumination, emotion regulation, and suicide attempts among teenagers aged thirteen to eighteen in Bandar Abbas who have attempted suicide at least once in 2023. Methods: The present research employed a descriptive design, which is a form of causal-comparative research. The statistical population comprised all teenagers who attempted suicide in 2023. The sample included 100 teenagers selected through convenience sampling. The data were collected using the Cognitive Emotion Regulation Questionnaire, the Nolen-Hoeksema Rumination Questionnaire, and the Ask Suicide-Screening Questionnaire. The data were analyzed using Pearson’s correlation coefficient and simultaneous regression. Results: The analysis of the main research hypotheses revealed a statistically significant positive correlation between rumination and suicide attempts (P<0.001). More precisely, the likelihood of suicide attempts increased with an increase in rumination among teenagers. Conversely, the correlation between overall emotion regulation and its dimensions was statistically significant and negative (P<0.001), suggesting that improvements in emotional regulation are associated with a decreased likelihood of suicide attempts among teenagers. Finally, the regression analysis showed that both rumination (β=0.49) and emotion regulation (β=-0.39) were statistically significant predictors of suicide attempts. Conclusion: The research results indicated that both emotion regulation and rumination are predictive factors for teen suicide attempts. Consequently, this finding represents a significant advancement in understanding factors contributing to suicide risk in this population.